PROFILE SEIZURES BANGKITAN PADA PASIEN DEWASA DI RUANG RAWAT INAP SARAF RSU RD KANDOU MANADO PERIODE JANUARI 2008 DESEMBER 2008 - *Karema Winifred (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND SEIZURES COULD HAPPEN TO ALL PEOPLE IN THE WORLD AFTER STROKE AND DEMENTIAS EPILEPTIC SEIZURES AND EPILEPSIES CONSTITUTE THE 3RD MOST FREQUENT NEUROLOGIC DISORDERS IN DEVELOPED COUNTRIES HOWEVER THERE ARE LIMITED PUBLISHED DATA ON THE EPIDEMIOLOGY AND ETIOLOGY OF SEIZURES AND EPILEPSY IN ADULT AND ELDERLY